2009
DOI: 10.1111/j.1365-2702.2009.02871.x
|View full text |Cite
|
Sign up to set email alerts
|

Parents’ experiences of a Family Support Program when a parent has incurable cancer

Abstract: The Family Support Program is described in detail in a manual that makes it easy for other health workers to use the same programme. The Family Support program was in use in outpatient clinics, oncology wards and palliative care units and was provided both from nurses and social workers trained in cancer care. Parent's in the study would like the Family Support Program to be available to all patients who receive the poor prognosis that their cancer cannot be cured.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
174
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(181 citation statements)
references
References 23 publications
6
174
0
1
Order By: Relevance
“…[31] Grossman highlighted that family support programmes, supportive and nurturing mothers, and no exposure to parents who are mentally ill, may help children to handle the double loss and bereavement better and reduce the risk of developing psychological problems. [29] Other studies, such as Bugge (2009), confirmed that when one of the parents is critically ill in divorced families, the parents' conflicts are reduced when they attend family support programmes, and that professionals may act as buffers between the ex-partners, and between the critically ill parent and the child. [26] Children need to be in dialogue with other family members, but Bugge showed that the children also need support, without having to think about family members' reactions.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…[31] Grossman highlighted that family support programmes, supportive and nurturing mothers, and no exposure to parents who are mentally ill, may help children to handle the double loss and bereavement better and reduce the risk of developing psychological problems. [29] Other studies, such as Bugge (2009), confirmed that when one of the parents is critically ill in divorced families, the parents' conflicts are reduced when they attend family support programmes, and that professionals may act as buffers between the ex-partners, and between the critically ill parent and the child. [26] Children need to be in dialogue with other family members, but Bugge showed that the children also need support, without having to think about family members' reactions.…”
Section: Resultsmentioning
confidence: 95%
“…The reference lists of these articles were checked for any other relevant studies, resulting in one more study by Bugge, Helseth and Darbyshire. [25,26] Eleven studies published from 1995 to 2009, and conducted in the USA (n = 7); UK (n = 1); Australia (n = 1) and Norway (n = 2) were finally included in the current integrative review. Six of the studies used a qualitative approach, whereas the other five studies were based on quantitative methods.…”
Section: Resultsmentioning
confidence: 99%
“…When parents wish to explain the illness they may not do it because they may not know how to tell them about the illness. On the other hand, children may find it hard to talk openly with parents about their thoughts and feelings concerning cancer because they can think they will increase their distress and because they may not know how to carry on this communication [3,11,12]. So it's very important to help children and parents to communicate with one another about the illness.…”
Section: Introductionmentioning
confidence: 99%
“…So the parent can have more difficulties in giving so much attention to the children as in the past and the children's needs may go unfulfilled [2]. A lot of studies indicate, as a consequence, that children of parents with cancer are at increased risk of developing psychological problems such as anxiety and mood disorders, psychosomatic problems, worsening of scholastic performance and difficulties in maintaining concentration [3][4][5][6]. They can also develop more aggressive behaviors with other children or with parents and feelings of guilt and shame.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation